Decreased quality of life and treatment satisfaction in patients with latent autoimmune diabetes of the adult - Minerva Granado-Casas; Montserrat Martínez-Alonso; Nuria Alcubierre; Anna Ramírez-Morros; Marta Hernández; Esmeralda Castelblanco; Joan Torres-Puiggros; Didac Mauricio (PeerJ, 2017)
Objectives Our main aim was to assess the quality of life (QoL) and treatment satisfaction (TS) of subjects with LADA (latent autoimmune diabetes of the adult) and compare these measures with those of patients with other diabetes types, i.e., type 1 (T1DM) and type 2 diabetes mellitus (T2DM). Methods This was a cross-sectional study with a total of 48 patients with LADA, 297 patients with T2DM and 124 with T1DM. The Audit of Diabetes-Dependent Quality of Life (ADDQoL-19) questionnaire and the Diabetes Treatment Satisfaction Questionnaire (DTSQ) were administered. Relevant clinical variables were also assessed. The data analysis included comparisons between groups and multivariate linear models. Results The LADA patients presented lower diabetes-specific QoL (p = 0.045) and average weighted impact scores (p = 0.007) than the T2DM patients. The subgroup of LADA patients with diabetic retinopathy (DR) who were treated with insulin had a lower ADDQoL average weighted impact score than the other diabetic groups. Although the overall measure of TS was not different between the LADA and T2DM (p = 0.389) and T1DM (p = 0.091) groups, the patients with LADA showed a poorer hyperglycemic frequency perception than the T2DM patients (p < 0.001) and an improved frequency of hypoglycemic perception compared with the T1DM patients (p = 0.021). Conclusions The current findings suggest a poorer quality of life, especially in terms of DR and insulin treatment, among patients with LADA compared with those with T1DM and T2DM. Hyperglycemia frequency perception was also poorer in the LADA patients than in the T1DM and T2DM patients. Further research with prospective studies and a large number of patients is necessary.